Smooth control of an articulated mobile robot with switching constraints. (2nd January 2016) - Tanaka, Motoyasu; Nakajima, Mizuki; Tanaka, Kazuo
Abstract : The paper describes a smooth controller of an articulated mobile robot with switching constraints. The use of switching constraints associated with grounded/lifted wheels is an effective method of controlling various motions; e.g. the avoidance of a moving obstacle. A model of an articulated mobile robot that has active and passive wheels and active joints with switching constraints is derived. A controller that accomplishes the trajectory tracking of the robot's head and subtasks using smooth joint input is proposed on the basis of the model. Simulations and experiments are presented to show the effectiveness of the proposed controller. Graphical Abstract: